Role of 2D material families in energy harvesting: an editorial overview - Raghavan, Prasanth; Ahn, Jou-Hyeon; Shelke, Manjusha (Journal of Materials Research, 2022)
The ever increasing proportion of an energy consuming society and the boost in industrialization accelerated the depletion of fossil fuel based energy sources at an alarming rate. This emphasizes the necessity of sustainable energy generation and storage to meet the daily energy demands. But, these alternative renewable energy sources like solar and wind power are intermittent and highly depend on weather, place and individuals. This creates the inevitability of suitable energy storage devices like batteries and supercapacitors. The interfacing of energy storing devices is required to maintain the supply chain equilibrium, power efficiency, regulate power fluctuations and reduce pollution. Besides, the boom in electric mobility and consumer electronics also require uninterrupted power supply. Hence, in the upcoming years the energy storing devices play a vital role in addressing the energy crisis. Innovations in new materials and technologies will be the core area of research and development in the coming future. 2D materials like graphene,transition metal carbides and nitrides (MXenes), transition metal borides (MBenes) and so on are the new class of materials among them MXenes are getting more attention in energy storage owing to its exceptional properties.

Exceptional cyclability of thermally stable PVdF-co-HFP/SiO2 nanocomposite polymer electrolytes for sodium ion batteries - Das, Akhila; Melepurakkal, Amrutha; Sreeram, Pranav; Gireesh, K. T.; Balakrishnan, Neethu T. M.; Fatima, M. J. Jabeen; Pullanchiyodan, Abhilash; Ahn, Jou-Hyeon; V. Shelke, Manjusha; Raghavan, Prasanth (Journal of Energy Storage, 2023)
Thermally stable composite polymer electrolyte (CPE) devising PVdF-co-HFP polymer with in-situ generated silica (SiO2) as filler is synthesised via non-solvent- induced phase inversion technique. The filler loading of in-situ synthesised silica in PVdF-co-HFP is varied from 0 to 9 wt% and its morphological, thermal and electrochemical characterization is carried out. Among the different composite electrolytes, the PVdF-co-HFP containing 6 wt% SiO2 shows the uniform microporous structure with a highest porosity (84 %), surface area (784.14 m(2) g(-1)), electrolyte uptake (262 %) and electrolyte retention value (0.48). The incorporation of in-situ SiO2 on CPE shows not only the enhancement in thermal stability but also reduced thermal shrinkage with an increase in the filler content. The electrochemical studies of PVdF-co-HFP containing 6 wt% SiO2 shows a higher ionic conductivity (0.71 mS cm(-1)) and potential stability >4.5 V verses Na/Na+. The Na-ion half-cells assembled with PVdF-co-HFP/SiO2 composite electrolyte show a specific capacity of similar to 120 mAh g(-1) at 0.3C rate in room temperature and a stable cycle performance with a Coulombic efficiency of around 100 % for 200 cycles.
Keywords: Composite electrolytes; Coulombic efficiency; polymer electrolytes; Sodium ion batteries; specific capacity; thermal stability